2013
DOI: 10.1007/s00276-013-1078-4
|View full text |Cite
|
Sign up to set email alerts
|

Split temporalis muscle flap anatomy, vascularization and clinical applications

Abstract: The duplication of the superficial temporal pedicle grants greater length compared to that of the deep pedicles, 57 mm versus 40 (p = 0.036). The middle temporal artery is capable of ensuring the vascularization, and therefore the viability, of the split flap. From these results, we spoke about the limitations of this study and we have inferred the main indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…there were several studies about the arterial and venous distribution on the anterior temporal area for the clinical consideration as to the flap surgeries [1,11,16]. Recently, lee et al described that the area extending 2.5 mm lateral and 3.0 mm superior to the uppermost superior orbital rim would be dangerous zone susceptible to injury of the superficial temporal artery (StA) [9].…”
Section: Discussionmentioning
confidence: 98%
“…there were several studies about the arterial and venous distribution on the anterior temporal area for the clinical consideration as to the flap surgeries [1,11,16]. Recently, lee et al described that the area extending 2.5 mm lateral and 3.0 mm superior to the uppermost superior orbital rim would be dangerous zone susceptible to injury of the superficial temporal artery (StA) [9].…”
Section: Discussionmentioning
confidence: 98%
“…In plastic and reconstructive surgery, several flaps for covering defects in the head and neck region are based on the blood supply of the STA [2,4,14,17,21,26]. Recently, it could be shown that the duplication of the superficial temporal pedicle grants greater length for facial reconstructions procedures by a split temporalis muscle compared to that of the deep pedicles [23]. Furthermore, the STA gains more and more importance for microsurgical free tissue transfer as a recipient vessel [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…En ellos se identificaron tres áreas: anterior, media y posterior, inervadas por los nervios TPA, TPM y TPP respectivamente. A diferencia de Chang et al 7 , quienes al utilizar la técnica de microdisección y posterior reconstrucción tridimensional describieron cinco ramos nerviosos que inervan regiones independientes: tres superiores por los nervios TPA, TPM, TPP y dos inferiores por el nervio bucal y el nervio mesentérico 6 . Sólo dos estudios en el mundo han aplicado el método de Sihler en el músculo temporal humano, en uno de ellos se realizó microdisección posterior a la tinción y se describe la existencia de un tronco nervioso principal que se dividió en dos ramos uno anterior y otro posterior en estrecha relación a la arteria temporal profunda 20 .…”
Section: Discussionunclassified
“…El músculo temporal se utiliza para realizar colgajos que reconstruyan defectos en el territorio craneofacial luego de la resección de un tumor de la cavidad oral, base de cráneo u órbita, así como para el tratamiento de la parálisis facial [1][2][3][4][5] , dependiendo de su uso el colgajo de músculo temporal puede ser dinámico o estático 6 . En el primer caso, donde se busca la funcionalidad muscular es indispensable el conocimiento profundo del patrón de inervación como por ejemplo en la técnica quirúrgica de Labbé 7 .…”
Section: Introductionunclassified